2022
DOI: 10.3390/polym14122389
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed PLA-Bioglass Scaffolds with Controllable Calcium Release and MSC Adhesion for Bone Tissue Engineering

Abstract: Large bone defects are commonly treated by replacement with auto- and allografts, which have substantial drawbacks including limited supply, donor site morbidity, and possible tissue rejection. This study aimed to improve bone defect treatment using a custom-made filament for tissue engineering scaffolds. The filament consists of biodegradable polylactide acid (PLA) and a varying amount (up to 20%) of osteoconductive S53P4 bioglass. By employing an innovative, additive manufacturing technique, scaffolds with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
(93 reference statements)
0
19
0
Order By: Relevance
“…This allows the continuous release of bioactive ions during the degradation process. The dose-dependent accumulation of calcium ions from the test particles in initially calcium-free PBS could be demonstrated by us[ 37 ]. The calcium concentration was about 0.35 nmol/µL after 7 days of incubation of a BG20 sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows the continuous release of bioactive ions during the degradation process. The dose-dependent accumulation of calcium ions from the test particles in initially calcium-free PBS could be demonstrated by us[ 37 ]. The calcium concentration was about 0.35 nmol/µL after 7 days of incubation of a BG20 sample.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate a possible influence of calcium ions released from BG20 on MSC, we performed an analogous experiment with BG20. Calcium ions were selectively bound by EGTA, and the amount of EGTA added was based on the expected calcium ion release, which was previously determined by colorimetric detection[ 37 ]. IL-6 gene expression was chosen as the readout parameter because it is rapidly and significantly downregulated by BG20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Moreover, the fabrication of ZrO 2 scaffolds through modern 3D printing techniques is laborious, and the attainment of desired scaffold design becomes a challenging task. 32 Other than the research investigations reported on bioactive calcium phosphate and bioglass reinforced 3D printed PLA scaffolds, [33][34][35] the studies on the development of 3D printed ZrO 2 based scaffolds have been rather scarcely documented. In this context, the present study aims to develop ZrO 2 based PLA scaffold through the FDM technique for its suitability in BTE.…”
Section: Introductionmentioning
confidence: 99%
“…Especially the use of multiple bioresorbable printing materials, such as polylactic acid (PLA) or polycaprolactone (PCL), adds further advantages. Trauma surgery and orthopedics, in particular, benefit from the possible applications ranging from use as bone substitute material [ 2 , 3 ], patient-specific implants [ 4 , 5 ], preoperative planning [ 6 ], use in teaching [ 7 ], or as protective equipment [ 8 ]. The requirements are as varied as the possible demands [ 1 ].…”
Section: Introductionmentioning
confidence: 99%